2019
DOI: 10.1002/cam4.2473
|View full text |Cite
|
Sign up to set email alerts
|

PTTG1 is involved in TNF‐α‐related hepatocellular carcinoma via the induction of c‐myc

Abstract: Hepatocellular carcinoma (HCC) is a malignant disease caused by a variety of factors. However, the genomic and molecular aberrations in HCC are largely unknown. Herein, pituitary tumor transforming gene 1 (PTTG1) was discovered as a potential inflammation‐related oncogene in HCC, and its functions and molecular mechanisms were investigated. mRNA expression microarray, real‐time polymerase chain reaction (PCR), immunohistochemistry, and western blotting analyses revealed that PTTG1 is upregulated in HCC. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…It should be noted that among these genes are those connected with viral infections as well as tumor progression. It proves that PTTG3P , PTTG1 and PTTG2 may function as oncogenes in HNSCC, similarly as was indicated in other cancers [ 17 , 30 , 31 , 34 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It should be noted that among these genes are those connected with viral infections as well as tumor progression. It proves that PTTG3P , PTTG1 and PTTG2 may function as oncogenes in HNSCC, similarly as was indicated in other cancers [ 17 , 30 , 31 , 34 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, the second member, PTTG1 , has been reported to promote migration and invasion in non-small cell lung cancer [ 11 ]. It has also been shown to play the role of an inflammation-related oncogene in hepatocellular carcinoma [ 31 ] Additionally, PTTG1 was found to induce epithelial–mesenchymal transition in colon carcinoma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enriched genes such as KIF18A [Luo et al 2018], MCM6 [Liu et al 2018], SKA1 [Xiao et al 2019] and ACTG2 [Wu et al 2017] were involved in invasion of hepatocellular carcinoma cells, but these genes may be associated with invasion of hepatoblastoma cells. Enriched genes such as PTTG1 [Lin et al 2019], CENPF (centromere protein F) [Li et al 2018], HJURP (Holliday junction recognition protein) [Chen et al 2018], MCM2 [Yang et al 2018], MCM7 [Qu et al 2017], RRM2 [Wang et al 2016], SGO1 [Wang et al 2015], NDC80 [Ju et al 2017], FOXM1 [Yu et al 2016], SKP2 [Wei et al 2018], TPX2 [Chen et al 2018], PLK4 [Bao et al 2018], NUF2 [Wang et al 2019], CENPK (centromere protein K) [Wang et al 2019], NCAPG (non-SMC condensin I complex subunit G) [Zhang et al 2018], BUB1 [Xu et al 2017], E2F5 [Sun et al 2016], RFC3 [Yao et al 2015], NCAPH (non-SMC condensin I complex subunit H) [Sun et al 2019], CCNB1 [Gu et al 2019], CDK1 [Gao et al 2018], CDC25C [Sun et al 2015], MAD2L1 [Li et al 2017], CDK6 [Zhu et al 2016], DKK1 [Zhang et al 2016], DKK4 [Chouhan et al 2016], DKK2 [Lin et al 2016] and LEF1 [Hu et al 2018] were important for proliferation of hepatocellular carcinoma cells, but these genes may be involved in proliferation of hepatoblastoma cells. High expression of enriched genes such as SPC25 [Chen et al 2018], MCM4 [Xie et al 2017], TYMS (thymidylatesynthetase) [Lee et al 2013], KNTC1 [Liu et al 2019] and CDH11 [Chen et al 2018] were responsible for advancement of various cancer types, but over expression these gene may be liable for progression of hepatoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, twenty genes were identified as hub genes. Unsurprisingly, some have been associated with HCC, such as CD20 [13], PTTG1 [14], CDCA5 [15], HSP90AB1 [16], CCT3 [17], SF3B4 [16], SETDB1 [17], VPS45 [18], RACGAP1 [19], USP21 [20, 21], and KIF20A [22]. In addition, we also found that MED24, FOXD2 and ZNF282 are associated with the progression from cirrhosis to HCC.…”
Section: Discussionmentioning
confidence: 99%